CURAHAN KEGIATAN SUAMI ISTRI DALAM RUMAH TANGGA TRANSMIGRAN - Suko Bandiyono (Populasi, 1994)
The study on the role of women in the community is always interesting to be carried out. This writing is a report on a study on the role of women in a migrant household focussing particularly on the work allocation of husband and wife in the transmigration area. The assumption which suggested that when the housewife has to work outside the transmigration settlement, and that the husband (who works in the transmigration settlement) then should take over all the domestic chores, has proved to be different from reality. Almost all of the household chores still remain to be performed by the women. This shows that women who work outside the transmigration settlement have to work extra harder and consume much more time in their activities. Even so, the domestic work allocation of a husband in their economic activities is larger than his wife. For this reason, both husband and wife of a migrant household have to perform a double role - although differently - in their capacity.